Dosimetric comparison among cyberknife, helical tomotherapy and VMAT for hypofractionated treatment in localized prostate cancer. Issue 50 (11th December 2020) - Serra, Marcello; Ametrano, Gianluca; Borzillo, Valentina; Quarto, Maria; Muto, Matteo; Di Franco, Rossella; Federica, Savino; Loffredo, Filomena; Paolo, Muto
Abstract : Abstract: Hypofractionation for localized prostate cancer treatment is rapidly spreading in the medical community and it is supported by radiobiological evidences (lower α/β ratio compared with surrounding tissues). Stereotactic body radiation therapy (SBRT) is a technique to administer high doses with great precision, which is commonly performed with CyberKnife (CK) in prostate cancer treatment. Since the CyberKnife (CK) is not available at all radiotherapy center, alternative SBRT techniques are available such as Volumetric Modulated Arc Therapy (VMAT) and Helical Tomotherapy (HT). The aim of the present study was to compare the dosimetric differences between the CK, VMAT, and HT plans for localized prostate cancer treatment. Seventeenpatients have been recruited and replanned using VMAT and HT to this purpose: they received the treatment using the CK with a prescription of 36.25 Gy in 5 fractions; bladder, rectum and penis bulb were considered as organs at risk (OAR). In order to compare the techniques, we considered DVHs, PTV coverage, Conformity Index and new Conformity Index, Homogeneity Index, beam-on time and OARs received dose. The 3 treatments methods showed a comparable coverage of the lesion (PTV 95%: 99.8 ± 0.4% CK; 98.5 ± 0.8% VMAT; 99.4 ± 0.5% HT. P < .05) and good sparing of OARs. Nevertheless, the beam-on time showed a significant difference (37 ± 9 m CK; 7.1 ± 0.3 m VMAT; 17 ± 2 m HT. P < .05). Our results showed that, although CK is the best SBRT technique for prostate cancer treatment, in case this technology is not available, it can be replaced by a similar treatment delivered by VMAT technique. VMAT can be administrated only if it has an appropriate Image Guided Radiation Therapy (IGRT) tracking system.